Membingkai Ulang Wu Chang sebagai Kultivasi Moral-Spiritual: Konvergensi dan Divergensi Etis antara Konfusianisme dan Pemikiran Moral Islam - Mahrani Siregar; Indra Harahap (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This article reframes Wu Chang—ren, yi, li, zhi, and xin—not merely as a set of social virtues in Confucianism, but as a framework of moral-spiritual cultivation that integrates self-formation, relational ethics, and alignment with Tian. It addresses a gap in existing scholarship, which has often treated Confucian morality descriptively or compared it with Islamic ethics through overly general moral parallels. Using comparative textual and conceptual analysis within the framework of comparative religious ethics, this study examines classical Confucian sources, selected works on Confucian ethics, and Islamic materials on prophetic moral virtues. The analysis argues that Wu Chang functions as a virtue-centered grammar of ethical self-cultivation whose public significance lies in the formation of compassion, justice, civility, wisdom, and trust. It further shows that Confucianism and Islamic moral thought converge in their concern for character formation and ethical responsibility, yet diverge in their metaphysical grounding, sources of normativity, and models of moral authority. By clarifying both convergence and divergence, this article contributes to comparative religious ethics and interreligious moral discourse in plural societies